ANALYSIS OF THE EFFECT OF CURRENT AND COOLING MEDIA IN TUNGSTEN INERT GAS (TIG) WELDING ON MECHANICAL STRENGTH AND MICRO STRUCTURE OF AISI 1045 STEEL FOR TRUSS FRAME MOTORCYCLE FRAME CONNECTIONS - Mohamad Indrawan; Aa Santosa (Universitas Majalengka, 2023)
AbstractCurrently, metal joining techniques in the field of welding have developed rapidly. In constructions that use metal raw materials, most of the joints are made by welding. Apart from joining, the welding process can also be used for repairs, for example to fill holes in castings, make coatings on tools, thicken worn parts and other repairs. Welding is also widely used for building construction, bridges, piping and automotive. As we know, there are many types of welding used today. One of them is Gas Tungsten Arc Welding (GTAW) or commonly called Tungsten Inert Gas (TIG).AISI 1045 steel is referred to as carbon steel because it complies with international coding, namely the 10xx series based on the nomenclature issued by AISI and SAE (Society of Automotive Engineers). The first number 10 is the code that indicates plain carbon, then the code xxx after the number 10 indicates the carbon composition. So AISI 1045 steel means carbon steel or plain carbon steel which has a carbon composition of 0.45%. Steel of this specification is widely used as a component of gears, shafts and bearings. According to its function, it must be able to withstand wear and tear due to friction with the chain. Wear resistance is defined as resistance to abrasion or resistance to dimension reduction due to friction